Gepuk Tea Business Development Strategy from a Sharia Economic Perspective in Pekanbaru City - Iqbal, Muhammad; Zalina, Indah; Mahyarni, Mahyarni (Kutubkhanah, 2025)
The growing growth of businesses operating in the food and beverage sector requires entrepreneurs to think creatively to compete with other entrepreneurs. One business sector that is currently very popular is food and beverages. Teh Gepuk is a beverage that is in demand by the people of Pekanbaru. The Teh Gepuk outlet entered the market in 2021, with four Teh Gepuk outlets spread across the Pekanbaru area. Business development carried out by Teh Gepuk owners in Pekanbaru City takes various steps to ensure the business runs according to plan. The purpose of this study is to determine the business development strategies that have been implemented by Teh Gepuk business owners to be able to compete with other entrepreneurs. Data analysis used in this study is a descriptive qualitative model with the Niles & Huberman model, the data collection method is in-depth interviews. The results of the study indicate that the business development strategy implemented by Teh Gepuk owners is using ingredients that do not contain haram substances, prioritizing a clean business environment, and avoiding things prohibited in Islam such as usury, maysir, gharar and tadlis in developing their businesses. The Teh Gepuk business owner's reason for opening his business was to create more jobs and expand outlets to generate more revenue and improve employee welfare. This aligns with Islamic economic principles.